GE_GERICHTE C/6189/2013 vom 14. März 2014 - GE Cour de justice (2014)
RÉQUISITION DE SÉQUESTRE; OPPOSITION(PROCÉDURE); ORDONNANCE DE SÉQUESTRE; VENTE; LETTRE DE CRÉDIT | LP.278; LP.271.1; LP.271.4; LP.272.1; CPC.320.A; CPC.320.B